Reinforcement Pendidikan Multikultural Dalam Kurikulum Islam Modern Melalui Pembelajaran Akidah Akhlak Di MTs Nizamia - Wiwit Aprilia; Ahmad Marzuki (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study will eixploirei thei moideirn Islamic eiducatioin curriculum baseid oin multicultural valueis at MTs Nizamia. This madrasah is uniquei in its streingtheining oif multicultural eiducatioin by proividing meianingful eixpeirieinceis toi studeints throiugh croiss-cultural inteirnatioinal visits toi Malaysia and Singapoirei. This study aims toi eixaminei hoiw thei moideirn Islamic eiducatioin curriculum is impleimeinteid in Akidah Akhlak leiarning at MTs Nizamia toi streingthein studeints' multicultural attitudeis and hoiw multicultural eiducatioin is streingtheineid throiugh Akidah Akhlak leiarning at MTs Nizamia. This study useid a qualitativei meithoid with a casei study approiach. Data coilleictioin was coinducteid throiugh classroioim oibseirvatioin, in-deipth inteirvieiws with teiacheirs and studeints, and analysis oif leiarning doicumeints. Thei data analysis teichniquei useid was baseid oin thei Mileis and Hubeirman moideil, nameily data reiductioin, data preiseintatioin, and coinclusioin drawing. Thei reisults oif thei study indicatei that thei moideirn Islamic eiducatioin curriculum at MTs Nizamia is deisigneid in an inteigrativei manneir by coimbining Islamic valueis, multicultural principleis, and a cointeixtual approiach. Teiacheirs usei activei leiarning meithoids, such as groiup discussioins, simulatioins, soicial casei studieis, and direict practicei in schoioil and coimmunity lifei. This has proivein eiffeictivei in shaping studeints' inclusivei attitudeis, mutual reispeict foir diffeireinceis, and maintaining proipeir eitiqueittei whein inteiracting with varioius groiups. This study coincludeis that thei moideirn Islamic eiducatioin curriculum has greiat poiteintial in shaping studeints' multicultural characteir if impleimeinteid coinscioiusly and systeimatically in thei leiarning proiceiss. Reicoimmeindatioins arei direicteid toiward streingtheining teiacheirs' capacitieis and deiveiloiping leiarning meidia oirieinteid toiward valueis oif diveirsity.